A novel method of anaerobic performance assessment in swimming - Smolka, L.; Ochmann, B. (The Journal of Strength and Conditioning Research, 2013)
The purpose of this study was to develop a novel, anaerobic efficiency test in swimming. The concept of this test was build upon the classic Wingate anaerobic test, with the difference that the dependent variables are extracted from an instantaneous speed curve. Twelve highly trained male swimmers, 19.3 (±3.3) years of age, 1.84 (±0.08) m in height, and 77 (±12.8) kg in weight, participated in the study. The swimmers swam a 100-m race in a 25-m pool, following the instructions to attain maximal swimming speed as quickly as possible and to keep maximal speed as long as possible. The race was recorded by means of video cameras (50 samples per second). Raw data were filtered by means of standard mathematical functions: smoothing and a polynomial function fit. The following speed parameters: maximal speed (Vmax), time to reach Vmax, time at Vmax, minimal speed (Vmin), and fatigue index were extracted from the filtered speed curve. Thorough assessment of anaerobic performance in swimming requires a swimming test leading to development of a speed curve obtained during a maximal effort race and not race time alone.